PENGARUH PENDIDIKAN KEWIRAUSAHAAN, PRAKTIK KEWIRAUSAHAAN, MOTIVASI, DAN LINGKUNGAN KELUARGA TERHADAP MINAT MAHASISWA UNTUK BERWIRAUSAHA DI MASA PANDEMI COVID-19 (Studi Kasus Pada Mahasiswa Angkatan 2018 Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Diyan Naturrohmah; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study was conducted to analyze how the influence of education, entrepreneurial practice, motivation, and family environment on student interest in entrepreneurship during the covid 19 pandemic. The case study in this study was a 2018 student majoring in accounting, Faculty of Economics and Business, Malang Islamic University. The number of samples that can be used in this study were 180 respondents who met the sample criteria. In this study using multiple linear regression analysis method. The results of this study simultaneously variable education, entrepreneurial practice, motivation, and family environment have a significant effect on interest in entrepreneurship. While partially 1) the education variable partially has a significant and positive effect on the interest in entrepreneurship, 2) the entrepreneurial practice variable partially has a significant and positive effect on the interest in entrepreneurship, 3) the motivation variable partially has a significant and positive effect on the interest in entrepreneurship, 4) the environmental variable Family partially has a significant and positive effect on interest in entrepreneurship.Keywords: entrepreneurial education, entrepreneurial practice, motivation, family environment, interest in entrepreneurship.